Study of the Density Distributions and Elastic form Factors of the Exotic Nuclei, 8He And 26F, Via the Three-Body Model - Sallh, Ghufran M.; Abdullah, Ahmed N. (Iraqi Journal of Science, 2021)
The matter, proton, and neutron density distributions of the ground state, the nuclear root-mean-square (rms) radii, and the elastic form factors of a two- neutron, 8He and 26F, halo nuclei have been studied by the three body model of within the harmonic oscillator (HO) and Woods-Saxon (WS) radial wave functions. The calculated results show that the two body model within the HO and WS radial wave functions succeeds in reproducing the neutron halo in these exotic nuclei. Moreover, the Glauber model at high energy (above several hundred MeV) has been used to calculate the rms radii and reaction cross sections of these nuclei.